(untitled) (Journal of the College of Languages (JCL), 2020)
This study aims to reveal the similarities and differences between Iraqi and Malay university learners and their genders in producing the supportive moves of criticism. To this end, 30 Iraqi and 30 Malay university learners have participated in this study. A Discourse Completion Test (DCT) and a Focus Group Interview (FGI) are conducted to elicit responses from the participants. Nguyen’s (2005) classification of criticism supportive moves is adapted to code the data. The data are analysed qualitatively and quantitatively. Overall, the findings unveil that both groups use similar categories of supportive moves, but Iraqis produce more of these devices than Malays in their criticisms. Although both females and males of both groups use identical devices, they differ in their preference for producing particular types. Iraqi and Malay females prefer to produce more supportive moves than Iraqi and Malay males in their criticisms. Finally, the study provides some pedagogical implications for teachers of English as a second and foreign language.